MACD Indicator with the Modified Signal Line and Trading Weight Inference in Fuzzy Environment - Boonprasurt, Prachya; Sampaokit, Pipat; Witayakiattilerd, Wichai (My University, 2022)
This research proposes improvements to moving average convergence divergence (MACD) by modifying the signal line. MACD with the modified signal line is called MACDP. It can signal trading faster than traditional MACD. The confidence level defined from a fuzzy logic process is applied to interpret the MACDP in each period. Furthermore, the research presents trading weight inference using a fuzzy logic process to increase the efficiency of trading. We analyze the recent stock movement of the SET100 group in the stock exchange of Thailand as a case study.
Keywords: fuzzy logic; Moving average; technical analysis; trading system